Impact of in vitro co-stimulation with of TLR2, TLR4 and TLR9 agonists and HIV1, on antigen-presenting cell activation (2015)
Objective: HIV-1 infects several immune cells including dendritic cells (DCs) and monocytes, which contributes in both to dissemination of HIV-1 infection and induction of antiviral immunity. These cells produce high amounts of type I IFN and proinflammatory cytokines upon Toll-like receptor (TLR) stimulation. During HIV-1 infection, an altered production of proinflammatory cytokines has been reported. However, the mechanisms underlying cytokine modulation have not been well described. Here, we evaluated the production of proinflammatory cytokines and activation of myeloid and plasmacytoid DCs and monocytes costimulated in vitro with TLR agonists and HIV-1. Methods: Changes in cytokine expression by real-time PCR and activation of DCs and monocytes by flow cytometry were evaluated after costimulation with HIV-1 and TLR agonists. Results: We observed an upregulation of TNF-α expression after TLR4 stimulation, but a downregulation of IL-6 when TLR2/TLR9 were stimulated. Interestingly, the expression of CD80 and CD86 costimulatory molecules in monocytes and DCs were significantly increased in cells challenged with HIV-1 and TLR2/TLR4/TLR9 agonists. Conclusion: This regulation of TNF-α and IL-6 production and changes in the expression of costimulatory molecules can be critical in the context of HIV-1 infection, by favoring the antigen-presenting cell activation through the stimulation of TLRs.